An Affirmative Fixed Point Result on b-Metric Spaces using (CLR) Property - Rao, V. S.; Dixit, U. (Journal of Scientific Research, 2023)
This study aims to show that four maps in a b-metric space that satisfy pairwise weak compatibility have common fixed points under certain conditions. In the main results of this paper, (CLR) property is employed, and common fixed points for four weakly compatible mappings are established. All our findings are backed up by befitting examples. Our results generalize and extend certain previous findings in the literature.